Sundanese Culture in The Framework Of Islam: Anthropological Analysis Of The Acculturation Process (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study examines the process of acculturation between Sundanese culture and Islam in the context of cultural transformation in the Sundanese region. The background of the research is rooted in the convergence of traditional values and Islamic influences that have been ongoing since the 14th century, resulting in a harmonious yet dynamic cultural synthesis. The aim of the study is to understand how Islamic values are adapted into Sundanese traditions and their impact on the social identity of the community. A qualitative approach employing participatory observation, in-depth interviews, and documentary study was used to extract rich empirical data. The research findings indicate that acculturation occurs through a negotiation of values across generations, leading to modifications in rituals, symbols, and social practices that preserve the essence of local culture while accommodating Islamic requirements. The implications of this study provide new insights into the adaptive dynamics of cultural interaction in the face of modernization and globalization, and have the potential to serve as a basis for developing cultural preservation policies that are responsive to contemporary changes.